Computer-Aided Design and Simulation of Spatial Opto-Mechatronic Interconnect Devices - Zeitler, Jochen; Reichle, Andreas; Franke, Jörg; Loosen, Florian; Backhaus, Carsten; Lindlein, Norbert (26th CIRP Design Conference, 2016, 2016)
Optical technologies become increasingly important in modern sensor and communication applications. Nevertheless, manufacturing and design methods in the field of spatial opto-electronics have not been investigated intensively yet. A new approach is to print polymer waveguides on spatial carriers to use the full design freedom of opto-mechatronic assemblies. Up to now, no specific design tools and validation methods are available. The article describes possible technology-specific methods for designing spatial opto-mechatronic applications with the focus on computer-aided design (CAD) and raytracing simulation of spatial waveguides.
Keywords: computer-aided design (CAD); design method; optical communication; opto-electronics; simulation